Bakteri Escherichia coli (E. coli) Pada Sarana Air Bersih Sumur Gali Di Kelurahan Hunggaluwa Kecamatan Limboto Kabupaten Gorontalo - Mustafa, Yanti; Suleman, Rahman; Pua Age, Sulastri; Jasin, Masri (LPPM Universitas Bina Mandiri Gorontalo, 2023)
Dug wells are a source of clean water that is needed by the community in general, so they must meet the physical, chemical and bacteriological requirements. The people in Hunggaluwa Village use dug wells to meet their needs for clean water for various purposes, be it washing, cooking, and others. The purpose of this study was to determine the condition of dug wells based on physical and bacteriological parameters. The results of the study showed that there were 22 dug wells made of strong, watertight materials and > 80 cm high (100%). For plastered wells, a minimum length of 1 m and a slope of 100 is 22 units (100%). For the distance between the well and the latrine, it was found that there were 17 wells <11 meters and 5 of them > 11 meters. Based on the content of Escherichia Coli (E.Coli) bacteria, there were 2 wells that met the requirements, and 20 wells that did not meet the requirements. Based on the results of research conducted by researchers, it can be concluded that: Escherichia Coli (E. Coli) Bacterial Content in Dug Well Clean Water Facilities (SGL) in Hunggaluwa Village,. It was concluded that the dug well (SGL) clean, 91% did not meet the requirements and 9% met the requirements.